Establishing a Halal Ecosystem to Eradicate Moral Degradation in Indonesian Education - Muhammad Umar Bahusin; Sakinah Izzati Nurrizqi; Ashifuddin Fikri; Salwa Hilda Febriza; Muhammad Dony Caprinosya; Muhammad Zakiy (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2024)
Moral degradation refers to a decline in a person's adherence to the social norms and ethical standards of society. This decline can be influenced by various factors, such as a child's environment and exposure to social media, which can lead to changes in behavior. As a result, this can disrupt the social order and contribute to feelings of social insecurity. In response to this issue, a research study was conducted to develop a "halal ecosystem" aimed at addressing moral degradation. The research employed qualitative exploratory methods, including in-depth interviews with teachers, students, child psychologists, and representatives of the Indonesian Child Protection Commission (KPAI) in Yogyakarta. The data collected was then analyzed through several stages, including data reduction, content analysis, validation, and drawing conclusions. The outcome of the research is the development of a system called Vedha Paho or Moral Science based on the Theory of Planned Behavior. This system comprises various elements designed to establish a halal ecosystem and create an optimal moral environment for child development.